Blockchain-based Settlement for Asset Trading - Jonathan Chiu; Thorsten V. Koeppl (Queen's University, Department of Economics, 2018)
Can securities be settled on a blockchain and, if so, what are the gains relative to existing settlement systems? We consider a blockchain that ensures delivery-vs-payment by linking transfers of assets with payments and operates via a Proof-of-Work protocol. The main problem is to overcome settlement fails where participants fork the chain to get rid of trading losses. To deter forking, the blockchain needs to restrict block size and block time in order to generate sufficient transaction fees which finance costly mining. We show that large enough trading volume, sufficiently strong preferences for fast settlement and limited trade size and risk are necessary conditions for blockchain-based settlement to be feasible. Despite mining being a deadweight cost, our estimates based on the market for US corporate debt show that gains from moving to faster and more exible settlement are in the range of 1-4 bps relative to existing legacy settlement systems.
Keywords: G2; H4; P43; 330; Securities settlement; Blockchain; Block size; Block time; Transaction fees; Club good